The Study of the Preliminary Forming Process of the Highly-Homogeneous Mixture Consisting of the Aluminum Powder – CNT in the Production Technology of Composite Materials - Vetkasov Nikolai (EDP Sciences, 2021)
The issue of the nanocomposites’ synthesis using of aluminum matrixes, reinforced with carbon nanotubes, with high physical and mechanical performance capabilities, as related to achieving of the homogeneous dispersion of carbon nanotubes in the composite’s aluminum matrix has been considered. Basics of the preparation technology have been developed and requirements for parameters of the so-called «normalized» mixture (highly-homogeneous in terms of volume of the dry mixture «aluminum powder – single-walled carbon nanotubes), intended for the efficient synthesis of composite granules by the mechanical alloying have been determined.